2013
DOI: 10.1155/2013/190981
|View full text |Cite
|
Sign up to set email alerts
|

Multiresolution Expansion and Approximation Order of Generalized Tempered Distributions

Abstract: Let K (R) be the generalized tempered distributions of-growth with restricted order N 0 , where the function () grows faster than any linear functions as | |. We show the convergence of multiresolution expansions of K (R) in the test function space K (R) of K (R). In addition, we show that the kernel of an integral operator K (R) K (R) provides approximation order in K (R) in the context of shift-invariant spaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Using the assumptions (1) (cf. (3)) and ( 2) on M, one verifies [25,26] that for every l ∈ N and |α|, |β| ≤ r, there exists C l > 0 such that…”
Section: Multiresolution Analysis In Distribution Spacesmentioning
confidence: 76%
See 3 more Smart Citations
“…Using the assumptions (1) (cf. (3)) and ( 2) on M, one verifies [25,26] that for every l ∈ N and |α|, |β| ≤ r, there exists C l > 0 such that…”
Section: Multiresolution Analysis In Distribution Spacesmentioning
confidence: 76%
“…In dimension n = 1, Pilipović and Teofanov [16] have shown that if f ∈ C r (R) and all of its derivatives up to order r are of at most polynomial growth, then its multiresolution expansion q j f with respect to an rregular MRA converges to f uniformly over compact intervals. Sohn has considered in [25] the analogous result for functions of growth O(e M (kx) ), but his arguments contain various inaccuracies (compare, e.g., his formulas ( 17) and ( 21) with our (3.7) below). We extend those results here to the multidimensional case and for the generalized multiresolution projections q λ,z with uniformity in the parameter z.…”
Section: Multiresolution Analysis In Distribution Spacesmentioning
confidence: 99%
See 2 more Smart Citations